Touching Imagination of Blind People: A Philosophical Perspective of Art (Journal of Social Sciences Review, 2023)
The cardinal aim of this article is to explore the philosophical elements in the literary scholarship of art and design by taking into account the specific theoretical perspectives and frameworks of representation, expressionism, form, and aestheticism. The relationship between art and philosophy is of great importance. In this study, the main objective of the researcher is to divulge blind people’s way of perceiving as well as imagining this world. The panoramic view of such people’s minds is portrayed in the particular artwork that is carried out on the basic parameters of the philosophy of art. The research also indicates how a piece of artwork in the domain of art and design can be proved very helpful as a tool to create as well as understand a particular situation while having some specific meanings. The symbolic and thematic concerns of the philosophy of artwork are also part of this research. This study concludes that the philosophy of art can help to depict a nice piece of artwork that can be further explored and analyzed while taking into account some particular critical approaches such as representation, expression, firmness, and aestheticism to unearth the hidden meanings, themes, and symbols. The symbolic significance of artworks within the paradigms of philosophy has never been ignored in any era.
Keywords: Philosophy; Art; Blind People; Representation; Touching Imagination